PENGARUH KUALITAS AUDIT DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ibrahim Ibrahim; Baiq Puteri Rabi’atul Adhawiyah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to determine the audit quality and managerial ownership affect earnings management in Manufacturing Companies listed on the Indonesia Stock Exchange. This data colletion uses secondary data obtained from financial statements using purposive sampling techniques. The population is all Manufacturing Companies listed on the Indonesia Stock Exchange in 2018 for a total of 170 company. While the samples taken amounted to 55 company. The result of the research variable data have been tested for classic assumptions in the form of normality assumptions, multicollinearity assummptions and heteroscedasticityassumptions. The method of analysisand using multiple linear regression techniques. The result of the study simultaneously showed that audit quality and managerial ownership had a significant effect on earnings management. The result of the study partially show that audit quality has a negative and significant effect on earnings management, while managerial ownership has no effect on earnings management.